Introduction of Leukotriene Receptor Antagonists in Manitoba - C Macie; K Wooldrage; J Manfreda; NR Anthonisen (Canadian Respiratory Journal)
Patient characteristics and prescribing patterns during the introduction of leukotriene receptor antagonists (LTRA) in Manitoba are described using the provincial health database. Residents of Manitoba with asthma, chronic obstructive pulmonary disease, bronchitis or claims for respiratory medications were identified. Six thousand forty-one of 160,626 (3.8%) patients received LTRA; the likelihood of receiving LTRA increased if a patient was younger than 15 years, lived in a rural locale, had asthma, had frequent physician visits or used inhaled corticosteroids. Subsequent prescriptions (68%) were associated with the number of physician visits and inhaled corticosteroid use, which were thought to be indexes of severity. Patients, especially children, who received more than five prescriptions showed evidence of increased asthma control, but there was little evidence of benefit in less selected patient groups due, at least in part, to poor compliance with all respiratory drugs.